A Role for Mediator Core in Limiting Coactivator Recruitment in Saccharomyces cerevisiae. Issue 2 (1st June 2020) - Yarrington, Robert M; Yu, Yaxin; Yan, Chao; Bai, Lu; Stillman, David J
Abstract: Mediator is an essential, multisubunit complex that functions as a transcriptional coactivator in yeast and other eukaryotic organisms. Mediator has four conserved modules, Head, Middle, Tail, and Kinase, and has been implicated in nearly all aspects of gene regulation. The Tail module has been shown to recruit the Mediator complex to the enhancer or upstream activating sequence (UAS) regions of genes via interactions with transcription factors, and the Kinase module facilitates the transition of Mediator from the UAS/enhancer to the preinitiation complex via protein phosphorylation. Here, we analyze expression of the Saccharomyces cerevisiae HO gene using a sin4 Mediator Tail mutation that separates the Tail module from the rest of the complex; the sin4 mutation permits independent recruitment of the Tail module to promoters without the rest of Mediator. Significant increases in recruitment of the SWI/SNF and SAGA coactivators to the HO promoter UAS were observed in a sin4 mutant, along with increased gene activation. These results are consistent with recent studies that have suggested that the Kinase module functions negatively to inhibit activation by the Tail. However, we found that Kinase module mutations did not mimic the effect of a sin4 mutation on HO expression. This suggests that at HO the core Mediator complex (Middle and Head modules) must play a role in limiting Tail binding to the promoter UAS and gene activation. We propose that the core Mediator complex helps modulate Mediator binding to the UAS regions of genes to limit coactivator recruitment and ensure proper regulation of gene transcription.